A Review of Attempts to Identification and Antifungal Susceptibility of Dermatophytes (Microsporum Canis and Tricophyton Mentagrophytes) Isolated from Infected Cats and Dogs with Experimental Dermatophytosis of Guinea Pigs - Sohir, Youssef; Rasha, M.Elkenany; Gamal, Younis (Journal of Veterinary Healthcare, 2023)
Dermatophytosis affect companion animal’s skin and keratin appendages as cats and dogs, resulting in red, scaly, itchy, bald, and raised patches like ring. The three main groups are Microsporum, Trichophyton and Epidermophyton. This study collected samples of skin scrapping and hairs from 130 cats and 70 dogs, using common mycological approach samples were examined. Antifungal agar disc diffusion and broth microdilution assays were utilized on some of the isolates. Three groups of Guinea pigs (6 in each) were then infected with one isolate of M. canis or T. mentagrophytes fungi, another skin scrapping samples of virulent fungi was isolated on the 7th and 14th days, blood samples were collected at 14th day. Reverse transcription-PCR to detect 98 bp protease gene. Resulting in 45% of cats and dogs tested positive for Microsporum and Trichophyton species. Agar disc diffusion revealed that the antifungal medication griseofulvin was the most effective against tested isolates. The best results for MIC test were griseofulvin (0.98 µg/ml) followed by acetic acid (0.28 µg/ml). Differential leukocytic count of Guinea pigs showed that monocyte levels remained unchanged, while neutrophil and lymphocyte levels had increased. The active (isolates from Guinea pigs skin scrapping) and dormant cells (isolates from keratin free media) were distinguished by Reverse Transcriptase-PCR. Collectively, qPCR is a successive and feasible method for the diagnosis for Microsporum and Trichophyton species.
Keywords: Antifungal; Microsporum canis; Trichophyton mentagrophytes; Dermatophytes; cats and dogs.